PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN MUSI RAWAS UTARA - Yanti Maryani Dalimunthe; Mulyadi Mulyadi (LPPM UNIVERSITAS BINA INSAN, 2017)
This research is conducted in Revenue Service, Financial Management and Asset of Regency of North Musi Rawas The formulation of problem in this research is Does work motivation influence to Dinas Pendapatan, Pengelolaan KeuanganDan Aset Daerah (DPPKAD) Kabupaten Musi Rawas Utara Regency of Musi Rawas Utara.Sampel research consist of 46 employees. Data collection techniques used questionnaires, observation and documentation. The analysis used in this study used multiple linear regression, Coefficient of determination analysis, concurrent test (F test), and t test. The result of research is 1) Training and Motivation have significant effect to employee performance, obtained value b1 = 0,068 and b2 = 0,650 and value a = 11,889, then the regression equation is: Y = 11,889 + 0,068 X1 + 0,650X2. 2) Motivation on Employee Performance shows that tcount = 3,782 is bigger than ttable = 1,683 with dk = 46 and significant level of sig = 0,001, this means that partially Motivation variable has significant influence to Employee Performance .3) Result of kofisien determinasi R equal to 0,845 and R2 equal to 72,9%. Value Fhitung = 92.142> Ftabel = 3.46 This means that Ho is rejected and Ha accepted.